Hedge Disclosures, Future Prices, and Production Distortions - Kanodia, Chandra; Mukherji, Arijit; Sapra, Haresh; Venugopalan, Raghu (Journal of Accounting Research, 2000)
Chandra Kanodia, Arijit Mukherji, Haresh Sapra, Raghu Venugopalan, Hedge Disclosures, Future Prices, and Production Distortions, Journal of Accounting Research, Vol. 38, Supplement: Studies on Accounting Information and the Economics of the Firm (2000), pp. 53-82